An evaluationof security issues in academic libraries: the case of Kenneth Dike Library, University of Ibadan (2012)
This study examined the security issues in academic libraries with particular reference to Kenneth Dike Library. The sample for this study includes 50 respondents comprising 15 professional librarians, 15 para-professionals and 20 non professional staff of the library. The study developed and utilized a 38 item questionnaire titled "Library Security Questionnaire (LSQ)" to elicit information from the respondents. Descriptive statistics was adopted using frequency counts and simple percentages in analyzing the data. The findings showed that theft and mutilation of library materials constitute a great security issue to the library system,training of staff on security issue is not adequate and that library staff in Kenneth Dike Library have a positive attitude toward the use and adoption of security systems to reduce theft and mutilation of library materials. Based on the findings it is recommended that proper stock taking exercise be carried out on monthly basis, porters as well as library assistants be trained regularly on security issues and that reprographic policies be reviewed as well as improved funding to install security systems to prevent theft and mutilation of library materials.